Self-Preferencing in E-Commerce Marketplaces: The Role of Sponsored Advertising and Private Labels - Long, Fei; Amaldoss, Wilfred (Marketing Science, 2024)
We study when and why a platform may seek to give preference to its private label in sponsored advertising.